Study of P and S Wave Quality Factor (Qα and Qβ) Around Mt. Jailolo - Emi Ulfiana; Wandono Wandono; Dimas Salomo Sianipar; Nova Heryandoko (Himpunan Ahli Geofisika Indonesia (HAGI), 2020)
Mt. Jailolo is a B type volcano that has never erupted after 1600. Seismic activities around Mt. Jailolo have never been recorded until the swarm in November 2015. Several studies have been done to determine thecause of the swarm, but it is not certain whether the cause of the swarm is tectonic or volcanic activities. The study of attenuation characteristics has never been carried out in the area around Mt. Jailolo. Attenuation characteristics are important to provide the medium information which seismic waves pass through and it can also be applied to the volcanic areas as preliminary disaster mitigation. The main objective of this study is to analyze attenuation characteristics often expressed by Quality factor (Q-factor) of P and S seismic wave (Qα and Qβ), which are inversely proportional to attenuation factor (1/Q). Calculations of Qα and Qβ are obtained using coda normalization method. The study area location is around Mt. Jailolo at 127.3◦ - 127.6◦E and 0.9◦ - 1.2◦ N. Data have been collected with 12 Short Period temporary 7G sensors network belongs to GFZ and BMKG. This study uses 147 swarm events from the sensors with a threshold magnitude of Mw< 5.0, during April 2017. The study obtains Qα(f) = 9.61814f 1.12981 and Qβ(f) = 19.10690f 1.22843. The current analysis concludes that the attenuation beneath Mt. Jailolo corresponds to the volcanic swarms which may have been triggered by its deeper layer’s magmatic activity.